OP0324 CANNABIDIOL ELEVATES INTRACELLULAR CALCIUM AND INDUCES APOPTOSIS IN HUMAN ARTICULAR CHONDROCYTES. (June 2019) - winklmayr, martina; Gaisberger, Martin; Fuchs, Julia; Kittll, Michael; Ritter, Markus; Jakab, Martin
Abstract : Background: Osteoarthritis (OA) is a major public health problem among the increasing aged and obese population, therefore development and investigation of new therapeutics is a major focus of OA research. Endocannabinoids (ECs), cannabinoids derived from the Cannabis sativa plant and synthetic cannabinoids have been attributed anti-inflammatory, antitumorigenic, analgesic and psychoactive effects. Over recent years increasing interest in the EC system as a target for therapeutic treatment of joint diseases has emerged [1]. Objectives: Cannabidiol (CBD) is the most abundant non psychoactive compound of Cannabis sativa extracts and has been shown to have anti-arthritic potency in animal models [2, 3]. In the present study we investigated the effects of CBD on the cell viability and Ca 2+ homeostasis in human articular chondrocytes. Methods: Cell viability, discrimination of intact, apoptotic and necrotic cells and caspase 3/7 activity were determined by Resazurin assays, Annexin-V/7-AAD staining followed by flow cytometry and caspase-Glo 3/7 assay respectively. Intracellular Ca 2+ was monitored by time-lapse fluorescence imaging. The perforated whole-cell patch clamp technique was used for measuring the cell membrane potential. Western blot analysis was performed for the quantification of Erk1/2 phosphorylation. Results: C28/i2 and human primary chondrocytes showed a significantly reduced viability with an apoptosis maximum at 10µM CBD after treatment with rising amounts of CBD. This apoptotic effect was accompanied by an increase of caspase 3/7 activity. Flow cytometry analysis of Annexin-V/7-AAD stained cells revealed a decline of intact cells and a significant dose dependent increase of the early apoptotic cell population after treatment with CBD. CBD significantly elevated intracellular Ca 2+ i accompanied by a depolarization of the cell membrane. This increase of Ca 2+ i was abrogated, when Ca 2+ was omitted from the bath solution indicating an influx of extracellular Ca 2+ rather than depletion of internal stores. Several blocking substances were tested to identify the channel/receptor responsible for this Ca 2+ influx. Cannabinoid receptor1 (CB1) antagonist AM251 significantly inhibited the Ca 2+ influx triggered by CBD. Moreover, preincubation of chondrocytes with AM251 significantly reduced the toxic effects of CBD. Looking for mediators of the apoptotic CBD effect downstream of the CB1 receptor enhanced Erk1/2 phosphorylation could be detected. However this Erk1/2 activation proved to be unaffected by CB1 receptor blockage. Conclusion: Micromolar concentrations CBD induce apoptosis in human articular chondrocytes. CBD also triggers an influx of extracellular Ca 2+ and potentiates Erk1/2 phosphorylation. The apoptotic effects are at least partially mediated by the CB1 receptor indicated by an increased cell viability and reduction of caspase activity after combined treatment with CBD and CB1 antagonist AM251. Since CBD induced Erk1/2 phosphorylation seems to be independent of CB1 signalling, the involvement of other signalling pathways and/or a crosstalk with other Ca 2+ channels or receptors seems likely and will be the focus of further investigations. References: [1] Staunton, C.A., A. Mobasheri, and R. Barrett-Jolley, High hopes for cannabinoid agonists in the treatment of rheumatic diseases. BMC Musculoskelet Disord, 2014. 15: p. 410. [2] Malfait, A.M., et al., The nonpsychoactive cannabis constituent cannabidiol is an oral anti-arthritic therapeutic in murine collagen-induced arthritis. Proc Natl Acad Sci U S A, 2000. 97(17): p. 9561-6. [3] Hammell, D.C., et al., Transdermal cannabidiol reduces inflammation and pain-related behaviours in a rat model of arthritis. Eur J Pain, 2015. Disclosure of Interests: None declared